Successful treatment of juvenile polyposis of infancy with sirolimus: a case report - Pei Xiao; Ting Zhang; Yizhong Wang; Yongmei Xiao; Xiaolu Li; Ruixue Wang; Youran Li; Ting Song (BMC, 2024)
Abstract Background Infantile Juvenile polyposis of infantile (JPI) is a rare and aggressive form of juvenile polyposis syndrome (JPS) typically diagnosed in the first year of life. It often carries a poor prognosis due to chronic gastrointestinal bleeding, protein-losing enteropathy, malnutrition and immune deficiency. Case presentation We report a case of a girl initially presented with pallor at 7 months of age, which progressed to gastrointestinal bleeding and protein-losing enteropathy. Endoscopic examination, which included both upper gastrointestinal endoscopy and enteroscopy, showed diffuse polyposis. Histopathology results indicated the presence of juvenile polyps with no dysplasia in all removed polyps. Genetic testing identified a 2.1 Mb deletion on chromosome 10q23.2q23.31 involving the phosphatase and tensin homolog (PTEN) and bone morphogenetic protein receptor type IA (BMPR1A) genes. Treatment with sirolimus initiated at 10 months of age led to a reduction in the need for blood and albumin infusions, improved patient growth, and quality of life. While the frequency of endoscopic evaluations decreased with sirolimus, regular endoscopic polypectomy every 5 months remained necessary. However, discontinuation of sirolimus resulted in polyp recurrence after 2 months due to pneumonia. Conclusion This case highlights sirolimus treatment can alleviate many complications of JPI, it does not eliminate the need for aggressive polypectomy.